2019
DOI: 10.1038/s41598-019-48232-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, awareness, treatment, and control of hypertension and their determinants: Results from the first cohort of non-communicable diseases in a Kurdish settlement

Abstract: Hypertension is a public health issue in iran. the study aimed to estimate the prevalence, awareness, treatment, and control of hypertension, and to explore their determinants among 10,040 Kurdish adults from Ravansar Non-Communicable Disease (RaNCD) cohort study in Iran. Univariate, and multivariate analyses were used for statistical analysis. Prevalence of hypertension was 15.7%. Among hypertensive patients, awareness, treatment, and control of hypertension were 80.7%, 73.2%, and 53.3%, respectively. In mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 53 publications
5
36
0
3
Order By: Relevance
“…In the current study, physical activity was associated with awareness and control, while Rajati reported that it was only associated with treatment (33). In addition, higher BMI was directly related to all three outcomes.…”
Section: Discussionmentioning
confidence: 45%
“…In the current study, physical activity was associated with awareness and control, while Rajati reported that it was only associated with treatment (33). In addition, higher BMI was directly related to all three outcomes.…”
Section: Discussionmentioning
confidence: 45%
“…Although most of measurements have been collected by self-report, the medical history and the type of received treatments have been checked by interviewers and general physicians. Validity and reliability of some of measurements have been reported elsewhere [17][18][19][20]. The principal investigators decided to use the online version of the questionnaire, in accordance with the PERSIAN cohort protocol [16].…”
Section: Methodsmentioning
confidence: 99%
“…Hypertension was de ned as having a systolic blood pressure (SBP) ≥140 mmHg and/or diastolic blood pressure (DBP) ≥90 mmHg, and/or currently taking antihypertensive drugs [19]. T2DM was de ned as having an FBS (fasting blood sugar) of ≥126mg/dl and/or being on diabetes medication and/or if the diabetes was con rmed by a health practitioner [20].…”
Section: Hypertension and Type 2 Diabetes Mellitus Assessmentmentioning
confidence: 99%